PENGARUH PERTUMBUHAN PENJUALAN DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSETS (ROA) - Euis Hernawati (POLITEKNIK PIKSI GANESHA, 2020)
This study aims to determine how much influence sales growth and working capital turnover have on return on assets at CV Magmaka Indonesia. The research method used is quantitative causal. The sample used is the company's financial statements for the 2017 period, then analyzed using multiple linear regression analysis. The results showed that there was a positive and significant impact simultaneously of sales growth and working capital turnover on return on assets. Partially, sales growth has a significant effect on return on assets and working capital turnover has no significant effect on return on assets.